Evaluation of adolescent sport specialization and injury mechanism by sex: A secondary analysis - Biese, K. M.; Post, E. G.; Schaefer, D. A.; Hernandez, M. I.; Brooks, M. A.; McGuine, T. A.; Bell, D. R. (Journal of Science and Medicine in Sport, 2020)
Objectives: The purpose of this study was to compare the association of sport specialization with previous overuse and acute injuries between male and female adolescent athletes. Design: Cross-sectional study. Methods: Questionnaires were completed by adolescent athletes from various sports at sport club summer events in the state of Wisconsin. Adolescent athletes (12-18 years old) who were active in organized sports in the previous year were recruited. The questionnaire contained demographics, sport participation, sport specialization classification, and previous injury history. Sport specialization classification was determined using common methods in sport specialization research. Previous injury was restricted to athletic injuries that occurred in the past year. Results: Two-thousand and eleven participants (age = 13.7 ± 1.6 years, females = 989) completed the questionnaire. Highly specialized athletes were more likely to report both acute and overuse injuries compared to low specialization athletes. However, this relationship differed by sex, with only moderate and highly specialized females being more likely (Moderate: OR [95%CI] = 1.74 [1.18-2.58], p = 0.005; High: OR [95%CI] = 1.69 [1.14-2.53], p = 0.010) to report an overuse injury compared to low specialization females. Highly specialized female athletes were more likely to report an acute injury (High: OR [95%CI] = 1.46 [1.06-2.02], p = 0.022) compared to low specialization females. Highly specialized male athletes were not associated with overuse or acute injuries. Conclusions: Highly specialized athletes were more likely to report acute and overuse injuries. However, when this analysis was separated by sex, only highly specialized females were more likely to report a previous overuse or acute injury.